Efficiency Analysis of Gold Pawn in Islamic Commercial Banks in Indonesia - Abdullah Haidar; Evania Herindar; Muhammad Syihabudin (UPT Pusat Studi Aswaja UNISNU Jepara, 2023)
Abstract Sharia pawnshops serve the lower middle class community by providing financial services. Furthermore, during the Covid-19 pandemic, sharia pawnshops were among the most popular financial institutions among those in need of short-term loans. Because of its high value and consistent demand, a pawnable asset, such as gold, is required to guarantee the loan. Furthermore, as competition in the sharia pawn industry grows, so does the presence of Islamic banking in the Indonesian gold pawn industry. The goal of this study was to examine the efficiency of the gold pawning product at five Islamic Commercial Banks (BUS) using a non-parametric Data Envelopment Analysis approach (DEA). In this study, an intermediate approach was used to determine input and output variables. The wadiah deposit bonus, general and administrative expenses, salaries and allowances, and other expenses are the input variables in this study. Meanwhile, the output variables are qardh loans, murabahah margin income, and other service income. According to the study's findings, the efficiency of sharia gold pawn products at BUS in Indonesia fluctuates between 2015 and 2020, with the average bank increasing efficiency during the COVID-19 pandemic. This study also looks into the possibility of improving inefficient programmes based on input and output variables; however, the results show that no potential improvement is needed because the initial data and projection are identical. This research can also be used to help other DMUs improve their efficiency.Keywords: Islamic Bank, Efficiency, DEA Analysis, Sharia Gold Pawn.AbstrakPegadaian syariah melayani masyarakat menengah ke bawah dengan menyediakan jasa keuangan. Selain itu, di masa pandemi Covid-19, pegadaian syariah menjadi salah satu lembaga keuangan yang paling banyak diminati oleh masyarakat yang membutuhkan pinjaman jangka pendek. Karena nilainya yang tinggi dan permintaan yang konsisten, aset yang dapat digadaikan, seperti emas, diperlukan untuk menjamin pinjaman tersebut. Selanjutnya, seiring dengan semakin ketatnya persaingan di industri gadai syariah, kehadiran perbankan syariah di industri gadai emas Indonesia juga semakin meningkat. Tujuan dari penelitian ini adalah untuk mengkaji efisiensi produk gadai emas pada lima Bank Umum Syariah (BUS) dengan menggunakan pendekatan Data Envelopment Analysis (DEA) non parametrik. Dalam penelitian ini digunakan pendekatan antara untuk menentukan variabel input dan output. Bonus simpanan wadiah, biaya umum dan administrasi, gaji dan tunjangan, serta biaya lainnya merupakan variabel input dalam penelitian ini. Sedangkan variabel outputnya adalah pinjaman qardh, pendapatan margin murabahah, dan pendapatan jasa lainnya. Berdasarkan temuan kajian tersebut, efisiensi produk gadai emas syariah pada BUS di Indonesia berfluktuasi antara tahun 2015 dan 2020, dengan rata-rata bank meningkatkan efisiensi selama pandemi COVID-19. Kajian ini juga melihat kemungkinan untuk memperbaiki program yang tidak efisien berdasarkan variabel input dan output; namun, hasil menunjukkan bahwa potensi peningkatan tidak diperlukan karena data awal dan proyeksi identik. Penelitian ini juga dapat digunakan untuk membantu DMU lain meningkatkan efisiensinya.Kata Kunci: Bank Syariah, Efisiensi, Analisis DEA, Gadai Emas Syariah.